1995
DOI: 10.1007/bf00175815
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of primary sequence and (G + C)% in determining the hierarchy of frequencies of complementary trinucleotide pairs in DNAs of different species

Abstract: To an approximation Chargaff's rule (%A = %T; %G = %C) applies to single-stranded DNA. In long sequences, not only complementary bases but also complementary oligonucleotides are present in approximately equal frequencies. This applies to all species studied. However, species usually differ in base composition. With the goal of understanding the evolutionary forces involved, I have compared the frequencies of trinucleotides in long sequences and their shuffled counterparts. Among the 32 complementary trinucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…In contrast, no relationship was detected between genomic G+C content and T opt for prokaryotes. Forsdyke (1995a) suggested that the rough equalities between C and G (respectively, A and T) contents in single-stranded DNA are the result of selection pressure favoring the evolution of numerous secondary structures in bacterial genomes. If such structures actually exist, the G+C content of genomic sequences should behave similarly to the G+C content of tRNA and rRNA with respect to temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no relationship was detected between genomic G+C content and T opt for prokaryotes. Forsdyke (1995a) suggested that the rough equalities between C and G (respectively, A and T) contents in single-stranded DNA are the result of selection pressure favoring the evolution of numerous secondary structures in bacterial genomes. If such structures actually exist, the G+C content of genomic sequences should behave similarly to the G+C content of tRNA and rRNA with respect to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Any deviations from PR2 would therefore be the result of deviation from the ideal no-strand-bias conditions, and these deviations are indeed correlated with the replication origin in E. coli, B. subtilis, Haemophilus influenzae (Lobry 1996a), and Mycoplasma genitalium (Lobry 1996b). The second interpretation is that PR2 is the result of a ''selection pressure favoring mutations that generate complementary oligonucleotides in close proximity, thus creating a potential to form stem-loops'' (Forsdyke 1995a). According to this hypothesis, deviations from PR2 are deviations from the ideal case, where the whole genome is involved in secondary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the low frequency of the dinucleotide TpA seems to be universal. The dinucleotide CpG is in low frequency in many taxa but in high frequency in most bacteria (Nussinov 1994;Forsdyke 1995d). However, base order is predominantly a local "strategy," influencing both codons and stem-loop stability.…”
Section: No Relationship Between Fors-d Value and (G + C)%mentioning
confidence: 99%
“…In this respect retroviral gehomes seem to offer a tractable model system for addressing general aspects of the speciation problem. Mechanisms by which percentage G + C differences might affect stem-loops and inhibit recombination are discussed elsewhere (Forsdyke 1995d). The importance of (G + C)% compatibility for recombination is emphasized by the observation that the high (G + C)% HTLV-1 genome is excluded from low (G + C)% sectors of the host genome (Zoubak et al 1994).…”
Section: Accelerated Speciation Modelmentioning
confidence: 99%
“…Thus, it is possible that the divergence may be ascribed, in part, to "TpA pressure," which is a "known" but not well understood pressure (Nussinov 1984;Alff-Steinberger 1987;Barrai et al 1991). TpA pressure affects all codons of general forms NTA and TAN (Forsdyke 1995d).…”
Section: Role For Tpa Pressure In Rhodobacter?mentioning
confidence: 99%